(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
In the last years, abortion has been one of the most discussed topics within the political, social and constitutional debate. The recent legal actions realized in this field, most notably the Dobbs v. Jackson judgment, show how women’s right to self-determine on their reproductive choices is still vulnerable and needs to be properly protected. The present paper aims at analyzing the French regulatory model on abortion rights and examining how the last legislative acts in this field are strengthening the right to abortion and its protection from a constitutional perspective.